Analysis of the Effectiveness of the Implementation of the Tax Volunteer Program in Improving Compliance With the Annual Tax Return Reporting of Individuals at KPP Pratama Menteng Satu Jakarta in 2020 – 2021 - Nabila, Amelia; Gangodawilage, Damith (Yayasan Sinergi Kawula Muda, 2023)
This study aims to analyze the effectiveness of the role of the tax volunteer program in improving compliance with the annual tax return reporting of individuals at the KPP Pratama Menteng one year 2020-2021 and determine the driving and inhibiting entities in the implementation of the tax volunteer program. The research phenomenon is the low realization of the tax revenue target, the low level of taxpayer compliance, whereas the Directorate General of taxes seeks to provide good services such as tax volunteer program. This thesis uses the theory of Duncan with indicators of achievement of objectives, integration and adaptation of this study using a qualitative research approach with descriptive research type . The Data used are primary data obtained from interviews and secondary data informants. Data collection techniques in the form of interviews , observation, documentation and source trigulation. The results showed that the effectiveness of the implementation of the tax volunteer program in improving the reporting of annual tax returns has been running according to Regulation article 1 point 9 PER-12/PJ/2021 but not yet effective, the main problem that is website unstable in Kpp Pratama Menteng one. and the part that became tax volunteers at Kpp Pratama Menteng one , only from the STIAMI Institut can be seen from the survey results because of good service in assisting the reporting of annual tax returns so that the tax volunteer program can have the opportunity to improve compliance and increase state tax revenue However, there are still inhibiting entities.